The mediating role of prosocial and antisocial behaviors between team trust and sport commitment in college basketball players. Issue 9 (2nd September 2022) - Tsai, Chi-Lun; Ju, Jie; Chen, Zuosong
ABSTRACT: Considering the popularity and particularity of basketball, the athletes face a potential "Sport Commitment Crisis" due to immense pressures from academics, training, employment, and college. To date, research in sports has demonstrated the relationship between coach trust and sport commitment; however, the relationship among teammates is yet to be explored. We examined whether teammate trust is related to commitment and if prosocial and antisocial behaviors mediate these relationships. Right before a game, the college basketball players ( N = 570) were asked to complete a multi-section questionnaire measuring the aforementioned variables. Structural equation modeling (SEM) revealed that athletes' perceptions of their teammates' trust were positively related to their sport commitment, and these relationships were mediated by teammate prosocial behavior. In contrast, antisocial behavior did not affect their relationship. The findings suggest that teammate trust could facilitate sport commitment in athletes, which could occur via prosocial behavior. Highlights: Current college athletes face multiple pressures such as academics, sports training, and future employment, which cause their continuous participation in sports training and competitions to be shaken, resulting in a decline in sport commitment. This study starts from the perspective of team atmosphere and peer behavior, and selects college basketball players on a large scale in China, because basketball is popular among Chinese college students and has brought greater social attention. In the process of playing basketball, the interaction between members is high, and the emotional factor with teammates is even more important. Therefore, the choice of research participants is also one of the advantages of this paper. GRAPHICAL ABSTRACT: UF0001